OL i Beijing - Markedskræfternes sejr over moralen! - Hansen, Jørn (Forum for Idræt, 2009)
Artiklen tager udgangspunkt i forståelse af, at når moralske argumenter ender med at være til fals, spiller økonomiske og magtpolitiske faktorer en afgørende rolle. I artiklen diskuteres menneskerettigheder, økonomi, sponsorer og politik i forbindelse med OL i Beijing 2008. The Olympic Games in Beijing – The Victory of Market Forces over Moral Despite the severe criticism against Beijing as host of the Olympic Games the number of influential state representatives from various countries at the opening ceremony had never been larger. In view of the strong moral criticism of the problems with the human rights in China, this is difficult to understand. Why did so many governments decide to support China and the Olympics in the end? This is one of the crucial questions to be answered in this article. The starting point of the analysis is the statement that the moral arguments were overruled by economic interests and the politics of power. Thus the article examines and points out Chinas powerful economic role and the role of some of the most important Olympic sponsors in the world economy with respect to questions of international politics.